2016
DOI: 10.1021/acs.chemmater.5b03857
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Energy Level Alignment within an Energy Cascade Organic Solar Cell

Abstract: The interfacial band alignment among boron subnaphthalocyanine chloride (SubNc), boron subphthalocyanine chloride (SubPc), and α-sexithiophene (α-6T) is explored using ultraviolet, inverse, and X-ray photoemission spectroscopies (UPS, IPES, and XPS, respectively). With these tools, the ionization energy (IE) and electron affinity (EA) for each material are determined. Layer-by-layer deposition of SubPc and SubNc on α-6T as well as SubPc on SubNc, combined with UPS and IPES, allows for the direct determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 38 publications
11
55
1
Order By: Relevance
“…To further validate our findings on the interface general energy map, we compared literature data on polymers and small molecules with our current model. By adding the literature data reported by various research groups into our universal energy map for both HOMO binding energies (see Figure S5a, Supporting Information) and interface dipoles (see Figure S5b, Supporting Information), we found that these data points follow the same trend as described in this Communication.…”
supporting
confidence: 65%
“…To further validate our findings on the interface general energy map, we compared literature data on polymers and small molecules with our current model. By adding the literature data reported by various research groups into our universal energy map for both HOMO binding energies (see Figure S5a, Supporting Information) and interface dipoles (see Figure S5b, Supporting Information), we found that these data points follow the same trend as described in this Communication.…”
supporting
confidence: 65%
“…In principle, FRET can collect more excitons to the charge‐separation interface if the energy acceptor is close to the interface. This exciton‐cascade strategy has been reported in PHJs . For efficient exciton collection at the D/A interface, the optical energy gaps of the stacked materials must be reduced gradually depending on the distance from the D/A interface, leading to sequential Förster energy transfer to the D/A interface .…”
Section: Photophysical Processes In Organic Photovoltaics Based On Plmentioning
confidence: 96%
“…This device was later replicated with some device optimization, yielding a slightly higher PCE of 3.09 % . Minor photocurrent contribution from tetracene was detected in the EQEs, but it is likely singlets being dissociated given the relatively shallow LUMO level of Cl‐BsubPc . The singlet fission process in tetracene is considered slow compared to materials like pentacene, where singlets are rapidly converted to triplets before dissociation can occur .…”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“…Compared to other electron donors that were initially optimized for fullerenes, α‐6T is better suited for pairing with BsubPc electron acceptors. This due to its broad, complementary absorbance (350 nm–550 nm) with many BsubPc and BsubNc derivatives, and shallower energy levels . The inherent surface roughness of α‐6T also facilitates charge dissociation at the donor/acceptor interface .…”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%